Effectiveness of anthelmintic therapy in the treatment of aelurostrongylosis in cats - Levytska, V.; Kravchenko, A. (Scientific Progress & Innovations, 2024)
Aelurostrongylosis in cats is a severe parasitic disease caused by the pulmonary nematodes Aelurostrongylus abstrusus. Effective treatment relies on combined approaches, including anthelmintic drugs, adjunctive therapies, and thorough monitoring of the animalʼs health status. This study aimed to evaluate the efficacy of different treatment protocols for cats with aelurostrongylosis and to identify optimal therapeutic approaches. The research was conducted at the "LikoVet" Veterinary Center (Uzhhorod, Ukraine) during 2023–2024. The study involved 18 cats diagnosed with aelurostrongylosis based on clinical signs, laboratory analyses, fecal examinations using the Baermann method, and radiographic imaging. The cats were divided into two groups to compare therapeutic efficacy: the first group received a combination of moxidectin, imidacloprid, prednisolone, amoxicillin with clavulanic acid, and oxygen therapy, while the second group was treated with fenbendazole according to the instructions. Therapeutic efficacy was assessed based on clinical improvement, reduction in larval counts in feces, and radiographic changes in the lungs on days 15 and 30 after treatment initiation. Before treatment, all cats exhibited signs of bronchitis, weight loss, coughing, lethargy, and anorexia. By day 15, significant clinical improvement was observed in the first group, with complete resolution of symptoms by day 30 and no larvae detected in fecal samples. In the second group, despite some positive clinical progress, two cats exhibited residual symptoms, and larvae were detected in 22.2 % of the animals after 30 days of treatment. The findings indicate the high efficacy of the combined therapy using moxidectin and imidacloprid, which resulted in complete clinical recovery of all cats in the first group. Fenbendazole treatment proved less effective, highlighting the superiority of combination therapy over monotherapy. The addition of corticosteroids, antibiotics, and oxygen therapy contributed to faster stabilization of cats with severe pulmonary syndrome. This study underscores the importance of a comprehensive approach to treating aelurostrongylosis in cats, which considers the severity of the infection, the necessity of intensive supportive care, and regular monitoring to achieve the best therapeutic outcomes.